(untitled) (Stamford Journal of English, 2013)
The role of woman is significant in the human world from the ancient time not only as a human being but also as an inseparable entity to take the mankind ahead with the time. The woman represents the symbol of nurture. She contributes to make progress in the family, society as well as country through her active participation same as the male counterpart. But woman is suppressed into lower status compared to the male power and position in the society intentionally, even after her great contribution in reality. The evidence can be found in the portrayal of woman in the literatures from the different cultures. How does the patriarchal society suppress the woman? How is the patriarchal ideology dominating the grand-narrative as well as molding the notion of womans psychology? In what ways, the voice of woman is controlled and represented with manipulative hegemony in unconstructive words? How is the woman fighting against the psychic violence to construct her self? Anita Desais Fire on the Mountain and Toni Morrisons The Bluest Eyes echo those thought provoking questions with ravenous eyes to discover the real female subject. Both writers exhibit the womans situation, emotion and realization which are scrutinized to observe the universality of female psyche. Stamford Journal of English; Volume 6; Page 230-248 DOI: http://dx.doi.org/10.3329/sje.v6i0.13916